If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(1 + 5x) + 15 = 13 + 5x (1 * 8 + 5x * 8) + 15 = 13 + 5x (8 + 40x) + 15 = 13 + 5x Reorder the terms: 8 + 15 + 40x = 13 + 5x Combine like terms: 8 + 15 = 23 23 + 40x = 13 + 5x Solving 23 + 40x = 13 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 23 + 40x + -5x = 13 + 5x + -5x Combine like terms: 40x + -5x = 35x 23 + 35x = 13 + 5x + -5x Combine like terms: 5x + -5x = 0 23 + 35x = 13 + 0 23 + 35x = 13 Add '-23' to each side of the equation. 23 + -23 + 35x = 13 + -23 Combine like terms: 23 + -23 = 0 0 + 35x = 13 + -23 35x = 13 + -23 Combine like terms: 13 + -23 = -10 35x = -10 Divide each side by '35'. x = -0.2857142857 Simplifying x = -0.2857142857
| 2x^2-x=10y | | X+.4X=82 | | -8x(-5x-6)=6x-22 | | 2(x-2)+5(2-x)=3(2x+2) | | (X-2y)(3x-5y)=3x^2+1xy-10y^2 | | 3n-4n=-14 | | -5a^2+260=0 | | -12x-48= | | 4x^2-9x-2.5=0 | | 25-3x=9-7x | | 5(4x+3)+6x-12= | | 4x^2+0.106x-0.106=0 | | 5x+7=-42-2 | | 2(6x+6)+4(10-x)= | | A=(4x-7) | | 2t-8=15 | | 2(x-2)+10(x+9)= | | 6x-5=13x+33 | | x^3=19x+30 | | 10v=-2 | | y=20+20x | | -10=s-(-6) | | 4log(4x)=12 | | X+17=204 | | 7s=-9 | | y=3x+-3 | | 10x-9=2x+11 | | (-3ln+6lnx)=6 | | 36*x^4=4.5 | | -5y+x=-3 | | x^2+0.106x-0.106=0 | | 9(x+2)=7x+25 |